KAJIAN ESTETIKA PADA BANGUNAN THE LAKEHOUSE CISARUA BOGOR - Putra, Alif Alfiandi; Rahayu, Tuntun (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
The Lakehouse is a restaurant located in Bogor which is located on Jl. Taman SafariNo. 101, Tugu Selatan, Kec. Cisarua, Bogor, West Java. The Lakehouse was completed in2018 with a footprint area of 4.1 Ha and a building area of 425 m2 with a contemporary modernconcept designed by Lukie Widya who uses his LUWIST Spatial design. This building islocated in the Pesona Alam Resort Area by applying a different concept to each floor, on the1st floor it is for a gathering area, the 2nd floor is a bar area, while the 3rd floor is used forprivate events with a direct view of the pine forest. The mass of the main building whichconsists of three floors is wrapped with exposed red brick material which makes it a focal point.Besides, this material dressing becomes a heating medium when the air is cold because it isvery suitable for the climate in this building, namely the climate of Bogor. With steelconstruction, the shape of this building is made rectangular and created by an artificial lake sothat it can create a connecting element between the building and the forest. The existence ofthis artificial lake is the main view after exploring the forest and the atmosphere becomes morelively because it is equipped with a sunken seating area where visitors can feel closer to thewater element. As a hardscape element, the existence of this lake makes the building moreharmonious